Analytical solution for lateral buckling of unburied subsea pipelines with distributed buoyancy section. (1st December 2017) - Wang, Zhenkui; Tang, Yougang; Wang, Chengze
Abstract: Unburied subsea pipelines operating under high temperature and high pressure (HT/HP) conditions tend to relieve their axial compressive force by forming lateral buckles. Uncontrolled lateral buckling can lead to pipeline failure. In order to control lateral buckling phenomenon, distributed buoyancy method is employed as buckle initiation technique. In this study, analytical solutions for lateral buckling of unburied subsea pipelines with distributed buoyancy section are derived. Fitting method is used to get the relationship between the equivalent axial compressive force and the half-length of the buckled section. The influence of the length and the weight of the distributed buoyancy section over typical behaviors of lateral buckling is illustrated and analyzed. The results show that increasing the length of distributed buoyancy section or decreasing the weight of distributed buoyancy section can all be used to decrease the minimum critical temperature difference and reduce the maximum axial compressive stress. However, the corresponding lateral displacement amplitude increases. The best selection of the weight of distributed buoyancy section is about half reduction of the original weight of pipeline. Highlights: Analytical solutions for lateral buckling of unburied subsea pipelines with distributed buoyancy section are derived. The influence of the length and the weight of the distributed buoyancy section over typical buckling behaviors is analyzed. The best selection of the weight of distributed buoyancy section is about half reduction of the original weight of pipeline.